PENGARUH LAMA PERENDAMAN SORGUM MANIS (Sorghum biocolor(L) Moench) DAN KONSENTRASI PENAMBAHAN KACANG TUNGGAK (Vigna unguiculata,(L) Walp) TERHADAP KARAKTERISTIK JAJA BANTAL - Evi Cahyani P, Ni Luh Putu; Yusa, Ni Made; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 2 (2016): Jurnal ITEPA, 2017)
This research is aimed o determine the effect of sweet sorghum immersion and cowpea concentration to jaja bantal characteristics. This research divied into two steps. At the fisrt step, sweet sorghum soaked in 4 treatment immersion time i.e 30,60,90, and 120 minutes were repeated 3 times. At this step, sensory’s score of the taste, colour, aroma, texture, and overall acceptance. Sweet sorghum with the best sensory’s score was continued into the second step. At the second step, sweet sorghum with the best sensory’s score added cowpea in making jaja bantal with 4 variant of concentration i.e 0, 0,06, 0,12, and 0,18% were repeated 3 times. Data were analyzed by analysis of variance and if there was a treatment effect on the observed parameters, then followed by duncan test. The best treatment showed 0,18% concentration of cowpea with water content 51,14%, ash content 3,32%, fat content 7,18%, protein content 8,48%, carbohydrate content 29,88% antioxidant capacity 2,58 (ppm), tanin 5,43 (ppm) and the best organoleptic second steps by 0,18 % concentration of cowpea with taste, colour, aroma, texture, and overall acceptance that liked by the panelist.
Keywords: jaja bantal, sweet sorghum, cowpea